ESTIMATING METHODS OF INVESTMENTS EFFICIENCY TO OWN GENERATION UNDER THE RISK CONDITIONS - O. V. Klimovets; V. A. Zubakin (Стратегические решения и риск-менеджмент)
The article is devoted to the assessment of the on-site generation effectiveness taking into account the risk associated with the uncertainty of future values of energy prices. It is shown that the economic efficiency is significantly affected by the unevenness of growth in energy prices and the correlation between load profile and graph of wholesale electricity prices.Restrictions on the applying existing approaches to evaluating the effectiveness of investment projects, based on calculation of uniquely defined cash flows, are approved. The paper shows the necessity of taking risks into account in order to increase the quality of decisions given the influence of energy resources prices on project’s economic efficiency and the uncertainty of future price values. Based on the analysis of quantitative methods of risk assessment it is proposed to use fuzzy-set approach as one of the most effective methods in the conditions of uncertainty of future values.